Optimizing irrigation strategies in wolfberry-alfalfa intercropping system in arid saline-alkali region: impacts on crop physiology, yield formation and quality parameters - Li, Haiyan; Wang, Yanbiao; Jiang, Yuanbo; Xie, Bojie; Qi, Guangping; Yin, Minhua; Kang, Yanxia; Ma, Yanlin; Wang, Yayu; Li, Boda; Chang, Wenjing (Frontiers in Plant Science, 2025)
Soil salinization caused by water scarcity in Northwest China severely limits agricultural sustainability. A forest-grass intercropping system combined with water regulation strategies can optimize soil and water resource use, reduce agricultural water stress, mitigate soil salinization, and promote sustainable and eco-efficient agricultural development in arid regions. In this study, based on a 3-year field experiment, four water regulation strategies were set up [upper and lower soil moisture limits were controlled by soil moisture content as a percentage of field water holding capacity θf, and full irrigation W0 (75%–85%θf), mild water deficit W1 (65%–75%θf), moderate water deficit W2 (55%–65%θf), and severe water deficit W3 (45%–55%θf)], the effects of water regulation on crop growth, physiology, yield and quality in wolfberry-alfalfa system were analyzed. The results showed that (1) increasing water deficit would limit the growth and development of wolfberry and alfalfa, with wolfberry and alfalfa growth being maximal at the vegetative growth stage-full flowering stage, and alfalfa plant height and stem thickness both being maximal in the first crop. (2) With the increase of water deficit, the chlorophyll content and photosynthetic characteristics of crops showed a decreasing trend. Among them, the daily dynamics of leaf photosynthesis showed that the net photosynthetic rate (Pn) and transpiration rate (Tr) of wolfberry presented a single-peak curve, the Pn, Tr and stomatal conductance (Cond) of alfalfa presented a double-peak curve, and the inter-cellular carbon dioxide concentration (Ci) of both of them reached the minimum from 12:00 to 14:00. (3) With the increase of planting years, the dry fruit yield of wolfberry and the total yield of alfalfa showed an increasing trend, while the crop quality all showed a decreasing trend; higher irrigation (W0 and W1) was more favorable to the crop yield and quality improvement. The multicriteria assessment showed that the W1 (65%–75%θf) treatment improved crop yield and quality in the wolfberry-alfalfa intercropping system while ensuring efficient water use. This treatment serves as a water control model for water conservation, yield increase, and quality improvement in the arid saline zone and similar ecological zones of northwestern China.